"Envelope wages" in the European Union. (December 2013) - WILLIAMS, Colin C.; PADMORE, Jo
Abstract: This article reveals how many formal employees in the European Union receive from their formal employer not only a declared wage but also an undeclared "envelope wage". Reporting the results of a 2007 survey involving 26, 659 face‐to‐face interviews, the authors find that one in 18 formal employees receives an envelope wage from their formal employer, amounting to 25 per cent of their gross pay on average. Such hybrid wage arrangements are ubiquitous, but are more common in some countries, employee categories and types of firm than others. The authors conclude by discussing the theoretical and policy implications of these findings.